The concept of the state in international relations : philosophy, sovereignty, cosmopolitanism - Schuett, Robert; Schuett, Robert; Stirk, Peter M. R., 1954-; Stirk, Peter M. R., 1954- (Edinburgh critical studies in Renaissance culture., 2015)
A critical reassessment of the concepts of the state and sovereignty in international relations theory. The concept of the state plays a central role in international relations, particularly in realist and neo-realist approaches. Yet, the meaning of the state is persistently taken to be self-evident by both advocates of the sovereign state and its critics. This volume counters this trend. It systematically considers the nature of the state, the concept of sovereignty and the challenges globalisation and cosmopolitanism. Featuring contributions from some of the most reputed theorists of the state, the essays in this collection give you a coherent and, at the same time, distinctively pluralist set of original reflections on the role and nature of the state.